Sectoral perturbation of quadratic spiral vortex beam - Bretsko, M.V.; Akimova, Ya.E.; Volyar, A.V.; Egorov, Yu.A.; Khalilov, S.I. (2022 VIII International Conference on Information Technology and Nanotechnology (ITNT), 2022)
This paper presents studies of the structural stability of a spiral beam subject to sector perturbations. Sector disturbance causes a change in the circulation direction of the Poynting vector streamlines in the disturbance region, which are caused by the appearance of single vortices with negative and positive topological charges. However, such perturbations do not cause a change in the orbital angular momentum of the beam, despite the increase in the number of vortex modes, and the perturbed beam remains structurally stable.